Aspects of Community Participation in the Management of Dayun Tourism Village - Nur Arini Yulia; Riau Nurita; Ahmad Nawawi (Jurnal Sosial Sains dan Komunikasi, 2024)
Community Participation Aspects in the Management of Dayun Tourism Village in the Organization of Economic Aspects, the following institutions related to the economic aspect are Bumkam, UMKM, Agricultural Groups, and Livestock Groups. This institution is a local economic development in Dayun Tourism Village. This institution not only functions as a facilitator in the management of resources and distribution of economic benefits, institutions in this aspect support the development of community businesses, expand employment opportunities, Forms of institutional participation in the economic aspect in Dayun Tourism Village in supporting tourism activities such as selling educational tour packages for tourists who buy tour packages provided by related institutions, providing tour guide services, managing the main artificial tourist attractions, namely Embung Terpadu, and selling regional souvenirs such as culinary products from watermelon and woven products, and batik to tourists. which can increase the attractiveness of tourist villages in a sustainable manner. in the aspect of cultural sustainability related to the LAMR Institution (Riau Malay Customary Institution), Bapekam, Sanggar Tari Sunting Melayang, and Cultural Heritage in the Perkumpulan Cucu Cicit Makam Tuk Antan Berdarah Putih group). In this institution, it is very crucial in maintaining the values of local traditions and cultural heritage to remain alive and relevant amidst the changing times, through solid collaboration between institutions, strengthening the role of the community such as involving the local community in providing performances to visitors and tourists in the form of tourist attractions such as the olang-olang dance, silat pangean, Pilgrimage to the Tomb of Tuk Antan Berdarah Putih Khalifa Kholil and participating in traditional events such as traditional wedding ceremonies that are carried out in everyday life. The role of the community in Dayun Tourism Village in organizations in the related creativity aspect is Pokdarwis (Tourism Awareness Group), MPA (Fire Care Community), PKK (Family Empowerment and Welfare) and Permata Waste Bank. The form of institutional participation in creativity to support tourism activities is in the form of increasing or creating tourist attractions in the eyes of tourists visiting Dayun Tourism Village, providing services in any form to provide comfort for visitors, and providing support for all tourism activities in Dayun Tourism Village.